Influences of Centella Asiatica and Curcuma Longa on Arterial Stiffness in a Hypertensive Animal Model - Hasimun, Patonah; Mulyani, Yani; Setiawan, Adinda R (Indonesian Journal of Pharmacy, 2021)
There is a strong relationship between arterial stiffness and high blood pressure. Arterial stiffness increases the risk of a cardiovascular event and sudden death, especially in hypertensive patients. This study aimed to determine the effective combination of Centella asiatica and Curcuma longa on arterial stiffness in hypertensive animal models. Twenty-five male rats aged 2-3 months were randomly into five groups. The groups comprising the negative control and positive control group (receiving drug carriers), the test drug group receiving captopril 2.5 mg/kg, the combination of Centella asiatica (CA) and Curcuma longa (CL) doses of 50 and 100 mg/kg. Except for the control group, all groups received a high-fat diet and 25% fructose drinking water for 28 days. On day 15, they received test medicines. On days 0, 14, and 28, systolic and diastolic blood pressures, as well as the PWV (pulse wave velocity), were assessed. Nitric oxide levels in serum were measured using Griess reagents on day 28. The results showed that a combination of CA and CL doses of 50 and 100 mg/kg reduced systolic and diastolic blood pressure accompanied by a decrease in PWV and a statistically significant increase in serum NO levels (p <0.05). It concluded that a combination of CA and CL has the potential as antihypertensive, improving arterial elasticity.